ANALYSIS OF COLLECTION PROCEDURES AND CALCULATION SYSTEMS FOR EARTH AND RURAL AND URBAN BUILDINGS IN HILIHAO VILLAGE, GUNUNGSITOLI DISTRICT - Maria Magdalena Bate'e (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
This writing is about the collection procedure and the land and building tax (PBB) calculation system in Hilihao Village, Gunungsitoli District. The purpose of this paper is to know the UN collection procedure, to know the UN calculation system, and to know the inhibiting factors and efforts to increase rural and urban PBB in Hilihao Village, Gunungsitoli District. The method used is descriptive qualitative. The results of this paper indicate that the rural and urban PBB collection procedure in Hilihao Village, Gunungsitoli City is based on Gunungsitoli Mayor Regulation Number 37 of 2013 concerning rural and urban PBB collection systems and procedures, starting from the stages of object registration procedures, object data collection, object assessment of SPPT issuance, payment , reporting. Whereas the rural and urban PBB calculation system in Hilihao Village refers to the Regional Regulation of Gunungsitoli City where the legal basis for the imposition of rural and urban PBB by the Regional Government is Law Number 28 of 2009. The rate for land and building tax for rural and urban areas (Rural and Urban PBB) which implemented in Hilihao Village, Gunungsitoli District, namely: 0.3% (zero point three percent) refers to the Gunungsitoli City Regional Regulation Number 2 of 2011 concerning Regional Taxes. Keywords: PBB collection procedure, PBB calculation system, Land and Building Tax